Handling missing items in the Exacerbations of Chronic Pulmonary Disease Tool. Issue 2 (12th May 2016) - Hitchings, Andrew W.; Baker, Emma H.; Jones, Paul W.
The Exacerbations of Chronic Pulmonary Disease Tool (EXACT) is a 14-item, self-administered daily symptom diary designed to identify and characterise exacerbations of chronic obstructive pulmonary disease (COPD). It provides a reliable, valid and standardised measure of exacerbation symptoms, and is sensitive to changes during recovery [1]. Scores are expressed on a 100-point scale, with higher values indicating worse symptoms or health state. In addition, the EXACT-derived E-RS (EXACT Respiratory Symptoms) provides valid daily COPD symptom scores [2, 3]. Electronic administration is recommended and has several advantages, notably in preventing item omission [4]. However, the expense of electronic solutions may prove prohibitive, particularly in noncommercial studies, when a pen-and-paper version may be used instead. In this context, it is important to have a method to deal with missing items. This is yet to be established. Within certain limits, missing items in the EXACT instrument can be imputed from the remaining answered items http://ow.ly/4mJQzP